Supervised versus unsupervised antimalarial treatment with six-dose artemether-lumefantrine: pharmacokinetic and dosage-related findings from a clinical trial in Uganda - Checchi, Francesco; Piola, Patrice; Fogg, Carole; Bajunirwe, Francis; Biraro, Samuel; Grandesso, Francesco; Ruzagira, Eugene; Babigumira, Joseph; Kigozi, Isaac; Kiguli, James; Kyomuhendo, Juliet; Ferradini, Laurent; et al. (Malaria Journal, 2006)
Background: A six-dose antimalarial regimen of artemether-lumefantrine (A/L) may soon become one of the most widely used drug combination in Africa, despite possible constraints with adherence and poor absorption due to inadequate nutrition, and a lack of pharmacokinetic and effectiveness data. Methods: Within a trial of supervised versus unsupervised A/L treatment in a stable Ugandan Plasmodium falciparum transmission setting, plasma lumefantrine concentrations were measured in a subset of patients on day 3 (C [lum]day3) and day 7 (C [lum]day7) post-inclusion. Predictors of lumefantrine concentrations were analysed to show how both C [lum]day7 and the weight-adjusted lumefantrine dose affect 28-day recrudescence and re-infection risks. The implications of these novel findings are discussed in terms of the emergence of lumefantrine-resistant strains in Africa. Results: C [lum]day3 and C [lum]day7 distributions among 241 supervised and 238 unsupervised patients were positively skewed. Unsupervised treatment and decreasing weight-adjusted lumefantrine dose were negatively associated with C [lum]day3. Unsupervised treatment and decreasing age showed strong negative associations with C [lum]day7. Both models were poorly predictive (R-squared < 0.25). There were no recrudescences in either arm, but decreasing lumefantrine dose per Kg resulted in up to 13-fold higher adjusted risks of re-infection. Re-infections occurred only among patients with C [lum]day7 below 400 ng/ mL (p < 0.001). Conclusion: Maintaining the present six-dose regimen and ensuring high adherence and intake are essential to maximize the public health benefits of this valuable drug combination.
Keywords: Antimalarial treatment; Artemether-lumefantrine; Pharmacokinetic; Uganda